Isomeric effects in structure formation and dielectric dynamics of different octanols. Issue 42 (25th October 2021) - Bolle, Jennifer; Bierwirth, S. Peter; Požar, Martina; Perera, Aurélien; Paulus, Michael; Münzner, Philipp; Albers, Christian; Dogan, Susanne; Elbers, Mirko; Sakrowski, Robin; Surmeier, Göran; Böhmer, Roland; et al.
Abstract : The microstructure of associated liquids promoted by hydrogen bonding is strongly constrained by charge order and steric hindrance which is demonstrated for the case of linear and branched octanols. Abstract : The understanding of the microstructure of associated liquids promoted by hydrogen-bonding and constrained by steric hindrance is highly relevant in chemistry, physics, biology and for many aspects of daily life. In this study we use a combination of X-ray diffraction, dielectric spectroscopy and molecular dynamics simulations to reveal temperature induced changes in the microstructure of different octanol isomers, i.e., linear 1-octanol and branched 2-, 3- and 4-octanol. In all octanols, the hydroxyl groups form the basis of chain-, cyclic- or loop-like bonded structures that are separated by outwardly directed alkyl chains. This clustering is analyzed through the scattering pre-peaks observed from X-ray scattering and simulations. The charge ordering which pilots OH aggregation can be linked to the strength of the Debye process observed in dielectric spectroscopy. Interestingly, all methods used here converge to the same interpretation: as one moves from 1-octanol to the branched octanols, the cluster structure evolves from loose large aggregates to a larger number of smaller, tighter aggregates. All alcohols exhibit a peculiar temperature dependence of both the pre-peak and Debye process, which can be understood as a change in microstructure promoted by chain association with increased chain length possibly assisted by ring-opening effects. All these results tend to support the intuitive picture of the entropic constraint provided by branching through the alkyl tails and highlight its capital entropic role in supramolecular assembly.